The Effect of 'CERDIK' Education on Knowledge Improvement among Hypertensive Patients - Amalia, Lia apriani; Stiexs, Anggie; Andora, Novika (Genius Journal, 2025)
Introduction: Hypertension is a major global health issue, affecting approximately one-third of adults and contributing significantly to morbidity and mortality. In Indonesia, its prevalence is rising, yet public awareness remains insufficient. The Ministry of Health has promoted the CERDIK framework—encouraging routine checkups, smoking cessation, physical activity, balanced diet, adequate rest, and stress management—as a key preventive measure. However, empirical evidence regarding its impact on patient knowledge in clinical settings remains limited. Objective: This study aimed to assess the effect of CERDIK-based health education on hypertension knowledge among patients at Sidowaras Primary Care Clinic, North Lampung. Methods: A quantitative pre-experimental design with a one-group pre-test and post-test approach was utilized. The population comprised 453 hypertensive patients registered between August and October 2024. Using accidental sampling and Slovin's formula, a sample of 27 Prolanis program participants was selected. Data were analyzed using the paired-samples t-test. Results: The analysis revealed a significant increase in knowledge following the intervention, with a p-value of 0.000 (<0.05). Conclusion: CERDIK health education effectively improves knowledge among hypertensive patients. Enhancing awareness and understanding of hypertension is crucial to preventing complications from non-communicable diseases. These findings support integrating CERDIK-based education into primary healthcare programs to promote better hypertension management.